Sustainable lipase production by Diutina rugosa NRRL Y-95 through a combined use of agro-industrial residues as feedstock - Freitas, M. (2021)
The potential use of alternative culture media towards the development of a sustainable bioprocess to produce lipases by Diutina rugosa is clearly demonstrated. First, a synthetic medium containing glucose, peptone, yeast extract, oleic acid, and ammonium sulfate was proposed, with lipase activity of 143 U/L. Then, alternative culture media formulated with agro-industrial residues, such as molasses, corn steep liquor (CSL), and olive mill waste (OMW), were investigated. An experimental design was conducted, and only CSL concentration was found to have a positive effect in lipase production. The highest lipase activity (561 U/L) was produced on a mixture of molasses (5 g/L), CSL (6 g/L), OMW (0.5\\% v/v), 0.5 g/L of ammonium sulfate, and 3 g/L of peptone at 24 h of cultivation. Lipase production was also carried out in a 1-L bioreactor leading to a slightly higher lipase activity at 24 h of cultivation. The semi-purified enzyme exhibits an optimum temperature and pH of 40 \textdegreeC and 7.0, respectively. Finally, the media cost per unit of lipase produced (UPC) was influenced by the medium components, specially by the inducer used. The lowest UPC was obtained when the agro-industrial residues were combined and used at the improved concentrations.